Including families in schizophrenia treatment: a systematic review - Iswanti, Dwi Indah; Nursalam, Nursalam; PK, Rizki Fitryasari; Mendrofa, Fery Agusman Motuho; Hani, Umi (International Journal of Public Health Science (IJPHS), 2023)
The family as one of system support for schizophrenia treatment in the primary care setting has been a challenge in integrating family services into mental health. This study aimed to review the urgent of family involvement during the treatment of schizophrenia in health mental services using the Family-Centered Care approach. A systematic review was performed using the population, intervention, comparison, outcome, study design (PICOS) framework within Scopus (27 articles), ProQuest (151 articles), Science Direct (93 articles), EBSCO (124 articles), and Springer (149 articles) published databases in the last five years using the keywords of “Family- Centered Care, nursing, AND Schizophreni*”. The articles were empirical quantitative, qualitative, or mixed-methods studies published within 2017- 2021 where study participants were clinically diagnosed with schizophrenia and intervention approaches were within the scope of family involvement. Twenty-four articles met the inclusion criteria for review. Evidence supports a professionally engaged relationship between patients, families, and providers with open knowledge exchange, communication, and collaboration. Family-centered care requires empathy, understanding, respect, and empowerment to choose, control decisions, and empower in the treatment of schizophrenia. This study concludes the importance of family involvement in the treatment of schizophrenia from the start. Health care providers help families through the admissions process.